2020
DOI: 10.1007/s10639-020-10373-3
|View full text |Cite
|
Sign up to set email alerts
|

Contextualized mobile game-based learning application for computing education

Abstract: This paper intends to present an overview of a mobile game-based learning application, BaghLearn that develops and upskills programming and algorithmic knowledge by cross-curricular capabilities through a traditional world-based game. The focus of this research was to explore the learning effectiveness of BaghLearn on students. Mixed method research approach was applied to collect, process and analyze the research data in which undergraduate students who had some prior knowledge or had taken algorithm courses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 38 publications
(49 reference statements)
0
16
0
Order By: Relevance
“…GBL is a type of educational game that improves students’ attitudes and approaches to learning and allows them to appreciate the learning process itself ( Yadav and Oyelere, 2020 ). Many studies have shown that digital game-based learning has a positive impact on learners’ motivation, attitude ( Tapingkae et al, 2020 ; Taub et al, 2020 ), engagement and performance ( Eltahir et al, 2021 ).…”
Section: Related Workmentioning
confidence: 99%
“…GBL is a type of educational game that improves students’ attitudes and approaches to learning and allows them to appreciate the learning process itself ( Yadav and Oyelere, 2020 ). Many studies have shown that digital game-based learning has a positive impact on learners’ motivation, attitude ( Tapingkae et al, 2020 ; Taub et al, 2020 ), engagement and performance ( Eltahir et al, 2021 ).…”
Section: Related Workmentioning
confidence: 99%
“…The foundations of the gamebased learning approach rely on the essence that learning can also occur subconsciously, whereas the learning experience and the incentives for engagement are further enhanced with elements that have been initially introduced in leisure games (e.g., quests, trophies, competition). Such elements have been positively correlated, in multiple studies, with increased motivational interest (i.e., engagement) and ultimately better outcomes in learning performance [68][69][70][71][72].…”
Section: Serious Gamesmentioning
confidence: 99%
“…Game-based learning encourages learners' participation in learning while playing and makes the learning process more interesting by adding more entertainment. Yadav and Oyelere (2020) stated that game-based learning also improves cognitive development and improves learners' learning motivation as both games and courses are combined. Although game-based learning is being used to review and reinforce, through constant advancement of this field, it has even allowed it to be used for prior learning of complicated subjects (Abdul Jabbar & Felicia, 2015).…”
Section: Game-based Learningmentioning
confidence: 99%